Synthesis of NiFe2O4/TiO2-Ag+ S-scheme photocatalysts by a novel complex-assisted vapor thermal method for photocatalytic hydrogen production - KERKEZ KUYUMCU, ÖZGE (My University, 2022)
© 2022 Elsevier B.V.This work aims to design and develop a photocatalyst with the main three properties: i) reduced bandgap for solar activation of the photocatalyst, ii) retarded e- / h+ recombination rate for the enhanced photocatalytic activity, iii) magnetic separability from the reaction medium. In this study, NiFe2O4/TiO2-Ag+ photocatalysts were synthesized to modify the structural properties of TiO2. Firstly, NiFe2O4 nanoparticles were synthesized by a conventional co-precipitation method, then in the presence of NiFe2O4 nanoparticles, TiO2 was synthesized by a novel complex-assisted vapor thermal (VT) method via slow hydrolysis of Ti-complex. After the best wt% amount of NiFe2O4 in the NiFe2O4/TiO2 had been determined for photocatalytic activity, Ag+ was added by wet-impregnation. The photocatalysts were characterized by X-ray diffraction (XRD), UV–vis Diffuse Reflectance Spectroscopy (DRS), Photoluminescence Spectroscopy (PL), vibrating sample magnetometer analysis (VSM), transmission electronic microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Photocatalytic hydrogen production reactions were carried out in methanol/water solution under solar light illumination. Consequently, the best configuration of the photocatalyst was determined as 12 wt% NiFe2O4/TiO2-0.5 wt% Ag+ (12NFT-0.50Ag+) which had shown the maximum hydrogen (H2) production rate as 137 µmol/g-cat after 5 h owing to its reduced bandgap energy and delayed e- / h+ recombination.
Keywords: Kimya Mühendisliği ve Teknolojisi; Fizik; Astronomi ve Astrofizik; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Physics; Astronomy and Astrophysics; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; MÜHENDİSLİK, KİMYASAL; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; SPACE SCIENCE; ENGINEERING, CHEMICAL; ASTRONOMY & ASTROPHYSICS; Genel Kimya; Fizik Bilimleri; Genel Kimya Mühendisliği; Genel Fizik ve Astronomi; General Chemistry; Physical Sciences; General Chemical Engineering; General Physics and Astronomy; Ag+ doping; Magnetic photocatalyst; NiFe2O4; Photocatalytic H2 production; TiO2; NiFe2O4; Photocatalytic H2 production; TiO2; Magnetic photocatalyst; Ag+ doping